Dissecting abdominal aortic aneurysm in Ang II-infused mice: suprarenal branch ruptures and apparent luminal dilatation. (23rd December 2014) - Trachet, Bram; Fraga-Silva, Rodrigo A.; Piersigilli, Alessandra; Tedgui, Alain; Sordet-Dessimoz, Jessica; Astolfo, Alberto; Van der Donckt, Carole; Modregger, Peter; Stampanoni, Marco F. M.; Segers, Patrick; Stergiopulos, Nikolaos
Abstract: Aims: In this work, we provide novel insight into the morphology of dissecting abdominal aortic aneurysms in angiotensin II-infused mice. We demonstrate why they exhibit a large variation in shape and, unlike their human counterparts, are located suprarenally rather than infrarenally. Methods and results: We combined synchrotron-based, ultra-high resolution ex vivo imaging (phase contrast X-Ray tomographic microscopy) with in vivo imaging (high-frequency ultrasound and contrast-enhanced micro-CT) and image-guided histology. In all mice, we observed a tear in the tunica media of the abdominal aorta near the ostium of the celiac artery. Independently we found that, unlike the gradual luminal expansion typical for human aneurysms, the outer diameter increase of angiotensin II-induced dissecting aneurysms in mice was related to one or several intramural haematomas. These were caused by ruptures of the tunica media near the ostium of small suprarenal side branches, which had never been detected by the established small animal imaging techniques. The tear near the celiac artery led to apparent luminal dilatation, while the intramural haematoma led to a dissection of the tunica adventitia on the left suprarenal side of the aorta. The number of ruptured branches was higher in those aneurysms that extended into the thoracic aorta, which explained the observed variability in aneurysm shape. Conclusion: Our results are the first to describe apparent luminal dilatation, suprarenal branch ruptures, and intramural haematoma formation in dissecting abdominal aortic aneurysms in mice. Moreover, we validate and demonstrate the vast potential of phase contrast X-ray tomographic microscopy in cardiovascular small animal applications.